2021
DOI: 10.4143/crt.2020.1015
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Tumoricidal Effects of Alpha-Lipoic Acid and Radiotherapy on Human Breast Cancer Cells via HMGB1

Abstract: Purpose Radiotherapy (RT) is one of main strategies of cancer treatment. However, some cancer cells are resistant to radiation-induced cell death, including apoptosis. Therefore, alternative approaches targeting different anti-tumor mechanisms such as cell senescence are required. This study aimed to investigate the synergistic effect of alpha-lipoic acid (ALA) on radiation-induced cell death and senescence in MDA-MB-231 human breast cancer cells.Materials and Methods The cells were divided into four groups de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…In addition to timesaving and cost reduction, drug repurposing has a significant advantage in ensuring safety through well-known pharmacokinetic and pharmacodynamic features. In the field of oncology, with the advent of metformin, immunotherapy, and alpha-lipoic acid, interest is increasing in drug repurposing of non-anticancer drugs to anticancer drugs [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to timesaving and cost reduction, drug repurposing has a significant advantage in ensuring safety through well-known pharmacokinetic and pharmacodynamic features. In the field of oncology, with the advent of metformin, immunotherapy, and alpha-lipoic acid, interest is increasing in drug repurposing of non-anticancer drugs to anticancer drugs [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…High mobility group protein B1 (HMGB1) is a highly conserved nuclear DNA‐binding protein related to a variety of cancer types, and its high expression is closely associated with tumor cell apoptosis, proliferation, and migration (Choi et al, 2021). Tao et al (2019) incubated human gastric cancer HGC‐27 cells with aloin for 24 hr and observed that cell viability was significantly decreased and morphological changes in apoptosis appeared in the nucleus under the influence of aloin.…”
Section: Resultsmentioning
confidence: 99%
“…High mobility group protein B1 (HMGB1) is a highly conserved nuclear DNA-binding protein related to a variety of cancer types, and its high expression is closely associated with tumor cell apoptosis, proliferation, and migration (Choi et al, 2021). and invasion potential.…”
Section: Gastric Cancermentioning
confidence: 99%
“…It downregulates furin, which, in turn, inhibits the maturation of IGF-1R [ 101 , 102 ]. Combining lipoic acid with radiation therapy was found to overcome the resistance to radiation therapy and promote apoptosis [ 103 ].…”
Section: Resultsmentioning
confidence: 99%